Innovative Approaches to Science and Social Studies-Centered Learning with a Focus on Student Wellbeing in Elementary Education - Helzi Helzi; Minsih Minsih; Anatri Desstya; Mazni Muhammad (Universitas Muhammadiyah Surakarta, 2024)
Science and Social Studies-centered learning in elementary schools has the potential to significantly enhance student wellbeing by addressing their holistic learning needs. This study seeks to examine how student wellbeing is integrated into the Science and Social Studies (IPAS)-centered curriculum for elementary students. Employing a qualitative research design grounded in a phenomenological approach, the study explores the lived experiences of students, teachers, and the school principal at Diponegoro Elementary School during the IPAS learning process. Data for this research were gathered through in-depth interviews, observations, and document analysis, with participants including teachers, the school principal, and students. Triangulation techniques were utilized to ensure data validity. The data analysis was conducted following the Miles and Huberman model, which comprises data reduction, data display, and conclusion drawing. The findings indicate that IPAS-centered learning has effectively integrated science and social studies through project-based learning initiatives, which actively engage students in practical, real-world applications. As a result, students have become more active and participatory, benefiting from hands-on activities within a supportive and conducive learning environment. This approach not only enhances learning outcomes but also underscores the importance of student wellbeing by fostering an integrated, holistic educational experience